Analisis Kasus Kecelakaan Lion Air JT610: Tinjauan Pidana dan Tanggung Jawab Korporasi dalam Keselamatan Penerbangan - Gatot Subroto Widagdo; Seti Citra Kadang Datu; Hamzah Robbani (Decisio: Jurnal Ilmiah Hukum, 2024)
In the modern era, air transportation has become a necessity for society, especially with the growth of the middle class in Indonesia. Although it brings advantages in terms of speed and comfort, the aviation industry also faces infrastructure and air traffic management challenges. On October 29 2018, the Lion Air JT610 crash tragedy occurred, killing all passengers and crew members. An in-depth analysis of this accident highlights issues of corporate responsibility and criminal law, demonstrating the complexity of responsibility in the aviation sector. This study applies a qualitative descriptive approach, which means this study describes the findings in a narrative format. From the competition between Boeing and Airbus to limited access to information resulting from investigations, this case highlights the importance of transparency, accountability and prioritizing safety in the aviation industry. The findings from the investigation should serve as a basis for improving and implementing more stringent safety standards in related industries. It is hoped that the lessons learned from this incident can avoid similar tragic incidents in the future.